The Effect of Asymmetric Intersexual Selection Power Perception on the Choice Deferral Behavior of Men and Women - Cheng-wen Jin; Rui Chen (Evolutionary Psychology, 2023)
Consumers always delay their choices, which can cause companies to suffer tremendous losses. One reason for such delay is a lack of confidence. Confidence in consumer decision-making can stem from many sources, including social power. In this research, we find that selection power with regard to choosing a romantic mate increases consumers’ decision confidence and, in turn, decreases choice deferral. We define the concept of intersexual selection power (ISP), and propose certain factors that can induce individuals’ asymmetric ISP. We conducted four studies to explore four factors that could influence consumers’ ISP perceptions (sex, mating cues, sex ratio, and mate value) and the effects of such power perception on choice deferral. The results showed that individuals with high ISP perception have more decision confidence and a lower choice deferral rate than individuals with low ISP perception regardless of the way in which choice deferral is measured.